Experimental and numerical analysis of flexural and impact behaviour of glass/pp sandwich panel for automotive structural applications. (4th July 2018) - Khan, M.A.; Syed, A.K.; Ijaz, H.; Shah, R.M.B.R.
Abstract : Cost and recyclability are among the primary factors on exploiting the engineering materials for their new applications. In this context, glass/pp-based sandwich panel has been studied experimentally and numerically with the aims of its potential applications in the automotive structures. The first part of this work presents the experimental results achieved for the load-carrying capacity of panels using three-point bend tests for its static flexural behaviour. Static behaviour is studied to compare the top-roller diameter effect on the flexural behaviour of the panels and shows a significant difference in the results. Impact behaviour of the panels is explored using three different types of impactor end-shapes that generate different levels of damage in the material with the same level of impact energy. The second part of this paper deals with the development of numerical models for the three-point bend and impact behaviour of the panels using a commercial finite element code of Abaqus. Strain energy-based homogenisation technique is employed to determine the equivalent orthotropic properties of complex circular honeycomb core material. The finite element models predict to a good level of the static and impact behaviour of the material when compared with the experiments.